Translation and validation of the Indonesian version of the chronic otitis media questionnaire-12 - Fakhriani, Rizka; Widuri, Asti; Yudistira, Danu (International Journal of Public Health Science (IJPHS), 2024)
Chronic suppurative otitis media (CSOM) is a pathological disorder affecting the ear, characterized by a persistent and long-lasting middle ear infection accompanied by the absence of an intact tympanic membrane. Multiple measures can be employed to evaluate the quality of life among patients with CSOM. One such instrument is the chronic otitis media questionnaire-12 (COMQ-12), which has demonstrated satisfactory levels of validity and reliability. The utilization of the COMQ-12 questionnaire has the potential to improve the quality of life experienced by CSOM patients. This study aimed to evaluate the validity and reliability of the Indonesian adaptation instrument of the COMQ-12 in patients with CSOM in the Otorhinolaryngology department of multiple hospitals in Yogyakarta. The study was conducted from February to July 2023. The study comprised 48 participants, consisting of 16 males and 32 females. The adapted Indonesian version of the COMQ-12 instrument demonstrates validity and reliability in assessing patients' quality of life with CSOM, as evidenced by a statistically significant r-value of 0.2353. The internal consistency analysis reveals that Cronbach's α coefficient is 0.868. The Indonesian adaptation of the COMQ-12 demonstrates validity and reliability as an assessment tool for measuring the health-related quality of life in patients diagnosed with CSOM.